Selection of Lentil Genotypes with Stable Yield and Protein Content across Diverse Environments - Dhakal, Krishna Hari; Pokharel, Monika; Dhakal, Deependra; Sapkota, Saroj; Darai, Rajendra (Journal of Agriculture and Forestry University, 2026)
Lentil (Lens culinaris Medik.) is a cool-season crop, rich in protein, dietary fiber, and micronutrients like iron, zinc and selenium with low fat. The effect of environment, genotypes and their interaction are important in determining yield and nutritional content of a crop. This study was designed to investigate the effects of genotype and environmental interaction on yield and grain protein stability in twelve lentil genotypes. Experiment was conducted at three diverse environments of Khajura (Banke), Khumaltar (Lalitpur) and Bijayanagar (Jumla) during winter season of 2020/21 using alpha lattice design with two replications. Data were recorded for days to flowering, days to maturity, plant height, number of pods per plant, number of seeds per pod, hundred seed weight, and grain yield. Protein content was analyzed by Kjeldahl method. The stability and genotype by environment interaction were examined with AMMI and GGE biplot methods. Results showed that yield and protein content are influenced by all of genotype, environment and genotype by environment interaction. Environment is identified as the leading factor in causing yield variation. Genotype X2011S-183-11 yielded (983 kg/ha) most stably of all among test environments in the panel of genotypes, although environment specific adaptation of genotypes to could be noted owing to their higher marginal yield at certain environment. The highest protein content was observed in the genotype X2011S-223-6 (25.0%) with better specific adaptation to Vijayanagar, Jumla while most stable expression of grain protein was found in genotype X2011S-125-23 (23.6%) across test environments. The tested genotypes can serve as valuable resource, in lentil improvement program, to breed for high and stable yield and grain protein content.